Implementasi Program Guru Penggerak dalam Meningkatkan Kompetensi Guru: Studi Multi Situs di Surabaya: Implementation of the Leading Teacher Program in Improving Teacher Competence: A Multi-Site Study in Surabaya - Ida Nuraini; Erny Roesminingsih; Yatim Riyanto; Amozi Khamidi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Improving teacher competence is very important to face challenges in the world of education, especially in terms of creativity and innovation in learning. The Teacher Mover Program is designed to overcome the problem of low teacher creativity and improve the quality of learning in schools. This study aims to examine the implementation of the Teacher Mover Program in improving teacher competence at SMPN 12 Surabaya and SMPN 32 Surabaya, with a focus on pedagogical development and teacher professionalism. The method used is descriptive qualitative with a data triangulation approach involving observation, interviews, and documentation. The results of the study indicate that pedagogical development through online training, mentoring, workshops, and learning communities can improve teacher competence in managing more effective learning. Teachers are also trained to master educational technology and apply more innovative learning methods, such as differentiated learning and student-centered learning. In addition, teacher professional development, which includes improving competence in learning, innovation, and creativity, also improves the quality of teaching. However, this study also found several obstacles, such as limited time for program implementation and inadequate facilities. To overcome these obstacles, it is recommended that schools allocate a special budget in the RKAS or collaborate with the private sector and parents. This study concludes that the Teacher Mover Program has proven to be effective in improving teacher competence in both pedagogical and professional aspects and must be supported by adequate policies and facilities for the sustainability of this program.